Spread of Multidrug Resistance through Mobile Genetic Elements in Dairy Products (Pakistan Journal of Science, 2024)
Various food and water sources contain antibiotic resistant microbiota. In this study, the resistance rate of antibiotics in bacteria isolated from food and water sources was checked. Promising isolates were identified as Bacillus safensis (MK934485), Pseudomonas putida (MK934486), Pseudomonas spp. (MK934484), Escherichia coli (MW713177, MW692366), Klebsiella spp. (MW713441).  Nine antibiotics were used to check resistance patterns of isolated strains. Resistance pattern observed high to low was Ampicillin (100%), Cefotaxime (82%), Ceftazidime (76%), Augmentin (52%), Cefixime (64%), Meropenem (17%). Escherichia coli showed resistance against Amoxicillin, Meropenem, Clarithromycin, Cefoxitin, and Cefuroxime. Klebsiella spp. were resistant against Cefuroxime, Cefoxitin, Clarithromycin, Meropenem and Amoxicillin.Strains showed MIC at 1000µg/ml of ampicillin. 20% isolates showed MIC at 300µg/ml of tetracycline. For streptomycin, 1000µg/ml MIC was calculated by 50% isolates. Detection forintI1 and Amp genes in the multidrug resistant bacteria, Pseudomonas spp., Escherichia coli and Klebsiella spp. showed the presence of class 1 integron. Gene intI1 from E. coli was found to have conserved domains of integrase. Results indicate that cycling of such pathogen through food is very common and poses a potential health risk to the consumer. Hence, precautionary measures are necessary to halt the progression of antibiotic resistance.
Keywords: ampgene; intI11gene; minimum inhibitory concentration (MIC); genetic elements; plasmid